Faktor-Faktor yang Mempengaruhi Pendapatan Petani Sawit Di Kecamatan Mersam Kabupaten Batanghari Jambi - Alpazri Alpazri (Science of Management and Students Research Journal (SMS), 2020)
This study aims to determine the effect of variable area of land, the amount of production, oil prices, variable costs, labor and income. In this study using primary data in 2018. The method used in this study is the method of multiple linear regression. Econometric analysis using multiple linear regression models is carried out to identify the variables that affect the income of oil palm farmers. From the values obtained it turns out that the f-count value is greater than the f-table value. This means that the area of land, the amount of production, the price of oil palm, variable costs, and labor have a significant effect on the income of oil palm farmers in the mersam subdistrict of Batanghari Regency, Jambi Province. The influence of the area of land on the income of oil palm farmers where the results of the t-value calculated on the area of land (X1) is -0.333 while the t-table with a 90 percent confidence level is 1.66365. Effect of Total Production on the income of oil palm farmers where the results of the t-value calculated at the Total Production (X2) is 1.863, while the t-table with a 90 percent confidence level is 1.66365. The effect of palm oil prices on the income of oil palm farmers where the result of the t-value calculated on the price of oil palm (X3) is 1.454 while the t-table value with a 90 percent confidence level is 1.66365. The effect of variable costs on the income of oil palm farmers where the results of the t-value of the variable cost (X4) is 0.605, while the value of t table with a 90 percent confidence level is 1.66365. The effect of labor force on the income of oil palm farmers where the result of the t-value of labor (X4) is 0.202, while the value of t table with a 90 percent confidence level is 1.66365. Seen t-count is smaller than the t-table, then Ho is rejected, Ha is accepted, which means that Labor has no effect and is not significant to the income of oil palm farmers in kecamtan Mersam, Batanghari Regency, Jambi Province. Thus the results of this study are expected to provide benefits in formulating effective and efficient policies and strategies in overcoming the problem of unemployment in Jambi Province.